Gas-sensitive sensor for detecting dissolved gas in oil, array of gas-sensitive sensor and preparation method of gas-sensitive sensor
By using MoS2-WS2 heterostructured material as the sensing material for gas-sensitive sensors, the problem of low detection accuracy of dissolved gases in oil in the prior art is solved, and high sensitivity and high selectivity gas detection is achieved, and oil-immersion type is supported. High-precision fault diagnosis of transformers.
Patent Information
- Application Number
- CN202411453444.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art has low accuracy, low sensitivity and low resolution when detecting dissolved gases in oil, making it difficult to achieve high-precision fault diagnosis of oil-immersed transformers.
Transition metal disulfides (TMDCs) are used as core sensing materials, and MoS2-WS2 heterostructure materials are synthesized by segmented hydrothermal and high-temperature vulcanization methods. They are gas-sensitive materials for p-n junction modified TMDCs and are deposited on the interfinger electrode. Form a gas-sensitive sensor.
It significantly improves the sensitivity and selectivity of the sensor to dissolved gases in the oil, improves the detection lower limit and response speed, enhances stability, and realizes high-precision quantitative detection of dissolved gases in the oil.
Smart Images

Figure CN119470569A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas sensors, and in particular to a gas sensor for detecting dissolved gas in oil, an array thereof, and a preparation method thereof. Background Art
[0002] Oil-immersed power transformers are widely used in power systems as necessary equipment for voltage conversion in transmission lines. Their stable working state is crucial to the safe operation of power systems. During long-term operation, insulation faults will inevitably occur inside oil-immersed transformers, including partial discharge, local overheating and insulation moisture, which will cause transformer oil leakage, fire and even explosion and other malignant accidents, seriously threatening people's lives and property safety and the stable and sustainable development of industrial production and social economy. When a fault occurs, the transformer oil will decompose and generate a series of stable gas components (mainly H2, CH4, C2H4 and C2H2) dissolved in the transformer oil. A large number of studies have shown that the types and concentrations of these gas components are closely related to the types and severity of insulation faults inside the transformer. Therefore, the insulation operating state of the transformer and the insulation fault of the feedback device can be evaluated by detecting the concentration and content of dissolved gas in the oil.
[0003] Dissolved Gas Analysis (DGA) in oil has become one of the indispensable methods for online monitoring of insulation faults in oil-immersed transformers because it is not affected by external electric and magnetic fields and can be performed when the transformer is energized. Among them, gas-sensitive sensing technology is the core of DGA. The detection accuracy of dissolved gas types and concentrations by this technology directly affects the reliability and stability of the diagnostic system. At present, dissolved gas sensor devices in oil mainly include semiconductor type, thermal conductivity type, catalytic combustion type and spectral type. Among them, thermal conductivity sensors have high requirements for the preparation process, resulting in expensive equipment, so they are less used; catalytic combustion sensors are only suitable for the detection of H2 or the total amount of combustible gas, and there is a catalyst that is easy to degrade and "poisoning" effect, which makes the sensing performance low or even ineffective; and spectral sensors are difficult to realize online monitoring technology under working conditions due to their inability to detect H2 (infrared spectrum), susceptibility to electromagnetic interference and complex operation.
[0004] Semiconductor sensors have the advantages of simple preparation process, low cost, high sensitivity and rapid response. They have played a huge role in the field of toxic, harmful and flammable and explosive gas detection, and are of great significance for atmospheric environment monitoring, industrial production control and prevention of fire and explosion accidents. With the vigorous development of nanosensing technology and artificial intelligence algorithms, the development of semiconductor nanosensor devices has provided a new idea for DGA. Combined with online data acquisition technology, the type and concentration of dissolved gas in transformer oil can be obtained in real time, which is expected to realize the discharge and overheating fault diagnosis of oil-immersed transformer equipment. However, at present, this type of sensor still has problems such as high operating temperature, low sensitivity and low resolution in the detection of dissolved gas components in oil.
[0005] Therefore, there is an urgent need to develop semiconductor resistive gas sensors and arrays suitable for the detection of dissolved gas in transformer oil, to achieve high-precision quantitative detection of dissolved gas components in oil, to realize the operating status evaluation and early fault diagnosis of oil-immersed transformers, and to promote the engineering application of semiconductor sensors in power systems. Summary of the invention
[0006] The embodiment of the present invention provides a gas sensor for detecting dissolved gas in oil, an array thereof, and a preparation method thereof, so as to solve the problem of low detection accuracy of dissolved gas in oil in the prior art.
[0007] In a first aspect, a gas sensor for detecting dissolved gas in oil is provided, comprising: a substrate, interdigital electrodes deposited on a surface of the substrate, and a pn junction modified TMDCs gas sensitive material attached to a surface of the interdigital electrodes;
[0008] The pn junction modified TMDCs gas-sensitive material is a MoS2-WS2 heterostructure material, and the molar ratio of W to Mo in the MoS2-WS2 heterostructure material is 1.3:1 to 1.7:1.
[0009] In a second aspect, a method for preparing a gas sensor for detecting dissolved gas in oil is provided, comprising:
[0010] Preparing a pn junction modified TMDCs gas-sensitive material, wherein the pn junction modified TMDCs gas-sensitive material is a MoS2-WS2 heterostructure material, and the molar ratio of W to Mo in the MoS2-WS2 heterostructure material is 1.3:1 to 1.7:1;
[0011] Mixing and grinding the pn junction modified TMDCs gas-sensitive material and ethylene glycol to obtain a mixed solution;
[0012] depositing interdigitated electrodes on the surface of the substrate;
[0013] The mixed solution was uniformly coated on the surface of the interdigital electrode and then dried at 150° C. for 12 h to obtain a gas sensor.
[0014] In a third aspect, a microsensor array is provided, comprising: a plurality of gas sensors as described in the embodiments of the first aspect.
[0015] Thus, the embodiment of the present invention utilizes transition metal disulfides as the core sensing material, and successfully synthesizes intrinsic and pn junction modified TMDCs with optimized performance by adopting segmented hydrothermal and high temperature sulfurization methods; by finely controlling key parameters in the synthesis process such as temperature, time and raw material ratio, high-quality preparation of WS2 and MoS2 is achieved; by adjusting the ion ratio of W and Mo, a MoS2-WS2 heterostructure is formed, which significantly improves the sensitivity and selectivity of the sensor to dissolved gases in oil; compared with the prior art, the gas sensor of the embodiment of the present invention shows obvious performance advantages in detection lower limit, response speed and stability, demonstrating its broad potential in practical applications, and has important practical value in the fields of oil monitoring and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0017] Figure 1 is a flow chart of a method for preparing a gas sensor for detecting dissolved gas in oil according to an embodiment of the present invention;
[0018] Figure 2 This is a brief schematic diagram of the preparation process of nano WS2;
[0019] Figure 3 This is a brief schematic diagram of the preparation process of nano-MoS2;
[0020] Figure 4 The invention provides a method for preparing a gas sensor using intrinsic MoS2 as an example;
[0021] Figure 5 It is an experimental platform for testing gas sensing performance;
[0022] Figure 6 It is the molecular structure of the gas dissolved in the oil;
[0023] Figure 7 Schematic diagram of the sensor array for detecting the identification technology of mixed components of dissolved gases in transformer oil;
[0024] Figure 8 It is the DBNN algorithm structure model;
[0025] Fig. 9 Schematic diagram of MPC and CDD of CO and C2H2 adsorbed on the surfaces of MoS2 and WS2; (a1)-(a3) MoS2 / CO system, (b1)-(b3) MoS2 / C2H2 system, (c1)-(c3) WS2 / CO system, (d1)-(d3) WS2 / C2H2 system;
[0026] Fig.10 Schematic diagram of MPC of CO and C2H2 adsorption on MoS2-WS2 surface, where (a1)-(a3) CO system, (b1)-(b3) C2H2 system;
[0027] Fig.11 Schematic diagram of CDD of CO and C2H2 adsorbed at the MoS2-WS2 heterojunction, where (a) CO system, (b) C2H2 system; the blue area is electron accumulation, the green area is electron depletion, and the isosurface is set to
[0028] Fig.12 Schematic diagram of the gas adsorption system BS, where (a)-(c) represent the MoS2, WS2 and MoS2-WS2 systems adsorbed by CO, (d)-(f) represent the MoS2, WS2 and MoS2-WS2 systems adsorbed by C2H2, and the black values are band gaps;
[0029] Fig.13 Schematic diagram of the sensing response of MoS2, WS2 and MoS2-WS2 to CO and C2H2 at room temperature. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The embodiment of the present invention discloses a gas sensor for detecting dissolved gas in oil. Specifically, the gas sensor comprises: a substrate, interdigital electrodes deposited on the surface of the substrate, and a pn junction modified TMDCs gas sensitive material attached to the surface of the interdigital electrodes.
[0032] Among them, the pn junction modified TMDCs gas-sensitive material is MoS2-WS2 heterostructure material.
[0033] Specifically, the molar ratio of W to Mo in the MoS2-WS2 heterostructure material is 1.3:1 to 1.7:1.
[0034] Preferably, the molar ratio of W to Mo in the MoS2-WS2 heterostructure material is 1.4:1.
[0035] Specifically, the substrate may be an aluminum oxide substrate, and the interdigital electrodes may be platinum interdigital electrodes.
[0036] The pn junction modified TMDCs are used as gas-sensitive materials, which have high sensitivity to gas and high adsorption capacity. The resistance change rate of the adsorption system is significantly improved. It is particularly suitable for the preparation of gas sensors. The prepared gas sensors are small in size and high in detection sensitivity, which is beneficial to the detection of mixed components of dissolved gas in transformer oil.
[0037] In addition, the embodiment of the present invention also discloses a method for preparing a gas sensor for detecting dissolved gas in oil. Specifically, the method comprises the following steps:
[0038] Step S101: preparing pn junction modified TMDCs gas-sensitive material.
[0039] Among them, the pn junction modified TMDCs gas-sensitive material is a MoS2-WS2 heterostructure material, and the molar ratio of W to Mo in the MoS2-WS2 heterostructure material is 1.3: 1 to 1.7: 1. In the prepared MoS2-WS2 heterostructure material, WS2 is n-type and MoS2 is p-type.
[0040] 1. In a preferred embodiment, the process of preparing the pn junction modified TMDCs gas-sensitive material is as follows:
[0041] Step 1: Prepare WO3·H2O and MoO3 respectively.
[0042] The preparation process of WO3·H2O is as follows:
[0043] Na2WO4·2H2O, H2C2O4·2H2O and HCl were heated at 92°C for 6 h, and then WO3·H2O was obtained by filtering, washing and drying.
[0044] WO3 precipitate (i.e. tungsten oxalate) is generated by the reaction of Na2WO4 and H2C2O4. Therefore, the molar ratio of Na2WO4·2H2O to H2C2O4·2H2O is generally 1:2. Ensuring precise control of the molar ratio between the reactants can maximize the yield of tungsten oxalate, while reducing unreacted starting materials and improving the purity of the reaction product. The pH of the solution can be adjusted by HCl to adjust the system to the required pH value, which is crucial for the formation of tungsten oxalate precipitate and other side reactions. The appropriate pH value helps to improve the selectivity and purity of the precipitate, better control the precipitation process of WO3 or dissolve unnecessary impurities. By controlling the amount of each raw material, the maximum conversion rate of the chemical reaction can be ensured, and the waste of raw materials can be avoided, so that the output can be effectively increased and the cost can be reduced on a production scale. Reducing unreacted chemicals can reduce the burden of waste treatment, which is environmentally friendly, especially in large-scale industrial production.
[0045] Na2WO4·2H2O is selected from analytical grade to ensure the purity of the raw materials. Na2WO4·2H2O, H2C2O4·2H2O and HCl can be placed in a beaker for heating. The heating method can be heated in a constant temperature water bath, and the temperature and time of the water bath heating can be precisely controlled to ensure that WO3·H2O is fully formed and has a good crystal structure. The filtration method can be centrifugal filtration, for example, centrifugation through a high-speed centrifuge to better remove unreacted substances or impurities. The cleaning process uses multiple washings to ensure the purity of WO3·H2O. The drying conditions should be strictly controlled to avoid structural changes in WO3·H2O at high temperatures. Specifically, low-temperature drying conditions are used, usually drying at room temperature or slightly above room temperature to prevent excessive temperatures from adversely affecting the product structure. The common temperature range is 20°C to 50°C. Maintain good ventilation during the drying process to promote the volatilization of moisture and prevent moisture from recombination during the crystallization process and affecting the structure of the product. Good ventilation can be achieved by providing sufficient air flow. Control the drying time to ensure that enough time is used to remove moisture from the product, but at the same time avoid excessive drying time that may cause product quality degradation or other adverse effects. The usual drying time ranges from 12 hours to 48 hours, depending on the drying temperature and the nature of the sample. Maintain a stable humidity level during the drying process to avoid the impact of excessive or low humidity on the product structure. Humidity control equipment or drying ovens can be used to ensure a constant humidity environment. Avoid severe shaking or vibration during the drying process to prevent mechanical damage or destruction of the product structure.
[0046] By strictly controlling the above drying conditions, the structural changes of WO3·H2O at high temperatures can be effectively avoided, thereby ensuring the quality and stability of the product.
[0047] Among them, the preparation process of MoO3 is as follows:
[0048] 1. Heat (NH4)2M2O7·2H2O at 500℃ for 2h in air atmosphere to obtain a solid product.
[0049] (NH4)2M2O7·2H2O can be placed in a first-stage heating tube for heating. High-temperature heating at 500℃ is the key to the formation of MoO3, and the heating rate and holding time should be strictly controlled. The heating rate is one of the important parameters affecting the formation of MoO3 during the heating process of (NH4)2M2O7·2H2O. In order to ensure that the key steps in the formation of MoO3 are effectively completed, the heating rate should be properly controlled. Generally speaking, the heating rate can be set to: 2℃ / minute to 5℃ / minute. By controlling the heating rate, the temperature can be prevented from rising too fast, resulting in the rapid volatilization of water in the product, causing uneven heating or other adverse reactions. Through a moderate heating rate, it can be ensured that the water gradually evaporates during the heating process and the product temperature rises evenly, which is conducive to the formation of a stable MoO3 product.
[0050] By introducing air, ensure that the heating environment is an oxidizing atmosphere.
[0051] 2. Heat the solid product, H2O2 and CTAB at 50°C for 2 h, and then obtain MoO3 by filtering, washing and drying.
[0052] The solid product, H2O2 and CTAB can be placed in a beaker for heating. The heating method can be water bath heating, and the MoO3 crystal growth can be more complete by heating in a 50°C water bath. The filtering method can be centrifugal filtration.
[0053] The dosage of (NH4)2M2O7·2H2O, H2O2 and CTAB should be reasonably designed according to the specific experimental conditions and the desired reaction results. These substances play different roles in certain synthetic reactions, such as catalysts, templates or surfactants. Therefore, the choice of mass ratio or molar ratio will affect the reaction rate, product morphology and the desired properties. By rationally selecting the mass ratio or molar ratio of (NH4)2M2O7·2H2O, H2O2 and CTAB, the morphology, structure and performance of the desired product can be regulated. H2O2 participates in the reaction as an oxidant and provides oxygen atoms to promote the redox reaction. CTAB, as a surfactant, regulates the dispersibility or morphology of the reactants, and in some cases also acts as a template to regulate the morphology and crystal structure of the product.
[0054] Strictly control the filtering, cleaning and drying processes to ensure the purity and integrity of the crystal structure of MoO3.
[0055] Step 2: Weigh the prepared WO3·H2O and MoO3 according to the molar ratio of W to Mo.
[0056] Step 3: The weighed WO3·H2O and MoO3 are respectively sulfurized with S powder at 800°C for 2h under an inert gas atmosphere, and then the sulfurized products are contacted or stacked to obtain a pn junction modified TMDCs gas-sensitive material.
[0057] For WO3·H2O, WO3·H2O can be placed in a reaction tube for sulfurization. Among them, the molar ratio of W to S is 1:5, which helps to obtain high-purity and high-crystallinity TMDCs. High-temperature heating at 800°C is a key step in the formation of WS2. It is necessary to ensure precise temperature control and sufficient heating time to obtain high-purity WS2.
[0058] For MoO3, MoO3 can be sulfurized in a second-stage heating tube. Among them, the molar ratio of Mo to S is 1:5, which helps to obtain high-purity and high-crystallinity TMDCs. The temperature, time and atmosphere control during the sulfurization process are also critical and have an important impact on the purity and performance of MoS2. A high temperature of 800°C helps complete sulfurization and improves the purity of the product.
[0059] The inert gas may be Ar gas. By introducing the inert gas, it is ensured that the vulcanization process is carried out in an oxygen-free environment, the material is protected from oxidation, and the release of harmful gases during the vulcanization process is avoided.
[0060] By sulfiding WO3·H2O and MoO3, two TMDCs materials, WS2 and MoS2, were generated. WS2 and MoS2 have different semiconductor properties, WS2 is a p-type semiconductor and MoS2 is an n-type semiconductor.
[0061] When p-type and n-type TMDCs materials are contacted or stacked by a specific method, they are merged together to form a pn heterostructure in the contact area. The formation of the heterostructure forms a space charge region of electrons and holes in the contact area, which is beneficial to the improvement of photoelectric conversion and gas sensing performance, thereby improving the performance of TMDCs gas sensing materials.
[0062] 2. In another preferred embodiment, the process of preparing the pn junction modified TMDCs gas-sensitive material is as follows:
[0063] Step 1: Na2WO4·2H2O, H2C2O4·2H2O and HCl are mixed and heated at 92°C for 6h, and then WO3·H2O is obtained by centrifugation, washing and drying.
[0064] Among them, the molar ratio of Na2WO4·2H2O, H2C2O4·2H2O and HCl is 1:1:1, which ensures sufficient reaction between the reactants and can effectively control the reaction rate and product formation.
[0065] Among them, Na2WO4·2H2O and H2C2O4·2H2O provide the source of W and C, while HCl provides chloride ions to promote the reaction. Their equal use can ensure sufficient contact between the reactants, thereby promoting the reaction. In addition, by keeping the molar ratio of the reactants equal, a stable reaction rate can be maintained during the reaction to avoid unnecessary side reactions or uneven reactions. Furthermore, this ratio can ensure the stable formation of the desired product and help obtain the desired product purity and crystal structure.
[0066] Na2WO4·2H2O, H2C2O4·2H2O and HCl can be placed in a beaker and heated. The heating method can be water bath heating. The filtering method can be centrifugal filtration to obtain solid precipitate WO3·H2O. HCl plays a role in adjusting the pH value.
[0067] Step 2: Weigh WO3·H2O and (NH4)2M2O7·2H2O according to the molar ratio of W to Mo.
[0068] Step 3: The weighed WO3·H2O and (NH4)2M2O7·2H2O are sulfurized with S powder at 800°C for 2h under an inert gas atmosphere to obtain a pn junction modified TMDCs gas-sensitive material.
[0069] Specifically, WO3·H2O and (NH4)2M2O7·2H2O can be placed in a reaction tube for sulfurization. Ar gas can be used as an inert gas to avoid the release of harmful gases during the sulfurization process and protect the substance from oxidation. A high temperature of 800°C helps complete sulfurization and improves the purity of the product.
[0070] 3. In another preferred embodiment, the process of preparing the pn junction modified TMDCs gas-sensitive material is as follows:
[0071] Step 1: Using a carbon sphere template, Na2WO4·2H2O and (NH4)2M2O7·2H2O are reacted at 180°C for 12 hours through a hydrothermal-template method to synthesize a carbon sphere complex of WO3 and MoO3.
[0072] The selection of the above reaction conditions is based on optimization experiments, aiming to ensure that the precursors are completely reacted to form uniform intermediate products and achieve the best reaction effect, while taking into account the convenience and cost-effectiveness of practical operations.
[0073] A series of comparative experiments were conducted by setting different reaction temperatures (such as 160°C, 180°C, 200°C) and times (6h, 12h, 24h), and characterization techniques such as XRD, SEM, and TEM were used to confirm the crystal structure and morphology of the material. By comparing the experimental results, it was shown that the selected parameters (i.e., 180°C and 12 hours) did optimize the performance of the material, and the material showed the best microscopic morphology and crystallinity, and a carbon sphere composite of WO3 and MoO3 with high crystallinity and uniform dispersion could be obtained.
[0074] In addition, it was found that proper atmosphere control (such as introducing nitrogen to maintain an inert environment) can effectively prevent oxidation and ensure the smooth progress of the reaction.
[0075] The hydrothermal reaction was carried out in a sealed reactor under natural atmosphere. The sealed environment ensured the stability of the reaction pressure and temperature and promoted the chemical reaction. For pn junction modified TMDCs, the molar ratio of W to Mo ions in the raw materials was adjusted to 1:1 to 10:1 before the hydrothermal reaction. The optimal molar ratio can be determined by experimental comparison, so that a heterojunction can be directly grown in the hydrothermal reaction, and a pn junction between n-type WS2 and p-type MoS2 can be formed in the subsequent further sulfurization.
[0076] Step 2: Calcine the carbon ball composite of WO3 and MoO3 at 600°C for 4 hours to remove the carbon ball template to obtain a hollow solid.
[0077] The above reaction conditions can completely remove the carbon sphere template while maintaining the structural integrity of the product. The parameter selection at this stage not only takes into account the removal efficiency of the carbon sphere template, but also fully considers the stability of the product structure and performance.
[0078] Step 3: Under an inert gas atmosphere, the hollow solid is sulfurized with S powder at 500° C. for 12 hours to obtain the pn junction modified TMDCs gas-sensitive material.
[0079] By comparing the effects of different vulcanization temperatures, times and amounts of sulfur source added on product performance, the selected vulcanization temperature is 500°C, the vulcanization time is 12 hours, and the amount of sulfur source added is 1.2 times the theoretical amount. Among them, the theoretical amount of sulfur source is (W+Mo) and the molar ratio of S is 1:5. This parameter combination can ensure the full progress of the vulcanization reaction and obtain high-quality WS2 and MoS2 solids. At the same time, the stable progress of the vulcanization process is achieved through atmosphere control (such as the introduction of inert gas to prevent oxidation) and precise temperature control.
[0080] After the preparation was completed, the gas sensor was tested for the actual application of dissolved gas detection in oil. By comparing the detection performance of different sensors under the same conditions, it was found that the newly prepared gas sensor showed excellent performance indicators in terms of detection limit, stability and repeatability. Compared with the existing technology, the gas sensor prepared by the new method has higher sensitivity and lower detection limit, showing obvious progress and advantages. Through full sulfurization, light yellow WS2 and dark black MoS2 solids were obtained respectively.
[0081] Through the preparation process mentioned above, the high-quality synthesis of TMDCs is ensured, and the crystallinity and stability of the material are improved.
[0082] Step S102: mixing and grinding the pn junction modified TMDCs gas-sensitive material and ethylene glycol to obtain a mixed solution.
[0083] Among them, the mass ratio of the pn junction modified TMDCs gas-sensitive material to ethylene glycol is 1:1, which helps to introduce ethylene glycol into TMDCs as a suitable additive. Ethylene glycol can introduce defects or adjust the lattice structure in TMDCs, thereby improving its gas-sensitive performance. By mixing with TMDCs in an appropriate proportion, effective regulation of the crystal structure and electronic properties of TMDCs can be achieved, thereby improving its gas-sensitive performance. In addition, the addition of an appropriate amount of ethylene glycol can help stabilize the crystal structure of TMDCs and improve the stability and reliability of the material. Ethylene glycol as an additive also helps to improve the processability of TMDCs, making it easier to form a uniform film or coating, which is beneficial to the practical application of the material.
[0084] The prepared mixed solution is viscous.
[0085] Step S103: depositing interdigital electrodes on the surface of the substrate.
[0086] Step S104: After the mixed solution is evenly coated on the surface of the interdigital electrode, it is dried at 150° C. for 12 hours to obtain a gas sensor.
[0087] The coating can be performed by an automated screen printer. When the gas-sensitive material is coated by an automated screen printer, the coating thickness and uniformity should be controlled, that is, during coating, it should be ensured that each part of the interdigital electrode is evenly covered with the gas-sensitive material and the thickness is consistent, so as to ensure the stable performance of the sensor.
[0088] After coating, the final drying stage begins. The drying equipment dries the coated interdigital electrodes at a specific temperature, allowing the solvent in the coating to gradually evaporate, and the coating becomes hard and firmly adhered. By precisely controlling the drying temperature and time, the quality and performance of the coating are ensured to be optimal.
[0089] During the entire preparation process, each component works together and each step is precisely controlled, thus ensuring that the final gas sensor has excellent performance and stability. From raw material synthesis to the completion of the final product, the efficiency and automation of gas sensor preparation are achieved, providing a reliable guarantee for practical applications.
[0090] In addition, an embodiment of the present invention further discloses a micro sensor array, comprising a plurality of gas sensors as described in the above embodiment. The micro sensor array is applied to the detection of dissolved gas in transformer oil.
[0091] The performance of the gas sensor and microsensor array prepared in the embodiments of the present invention is evaluated below, and the performance of the pn junction modified TMDCs gas-sensitive material with W ion:Mo ion=1.4:1 and the gas sensor prepared therefrom are characterized and evaluated.
[0092] First, the intrinsic and pn junction modified TMDCs were characterized from all aspects, including microscopic morphology, crystal phase, crystal plane composition, elemental composition, specific surface area, and grain size. Combined with the material characterization results, the effects of different types and doping amounts of pn junctions on the physical and chemical properties of TMDCs gas-sensitive materials were analyzed. The band structures of the intrinsic and pn junction modified TMDCs were measured by ultraviolet photoelectron spectroscopy (UPS) combined with ultraviolet-visible diffuse reflectance spectroscopy (UV-Vis-DRS), confirming that the synthesized WS2 and MoS2 exhibit n-type and p-type characteristics, respectively, and exploring the carrier properties of the system after pn junction modification with different types and doping amounts.
[0093] The synthesized pn junction modified TMDCs gas-sensitive materials (i.e., MoS2-WS2 heterostructures with different doping ratios) were used in transformer oil dissolved gas (CO and C2H2) experiments. The study found that among the synthesized pn junction modified TMDCs, the MoS2-WS2 heterostructures with a molar ratio of W ions to Mo ions of 1.3:1 to 1.7:1 have stronger adsorption and charge transfer properties. Among them, the MoS2-WS2 heterostructure with a molar ratio of W ions to Mo ions of 1.4:1 has the strongest adsorption and charge transfer properties.
[0094] The comparative analysis of MoS2-WS2 heterostructure (W ion: Mo ion = 1.4:1) with MoS2 and WS2 is as follows:
[0095] Based on the geometric structures of MoS2, WS2 and MoS2-WS2 heterostructures (W ion: Mo ion = 1.4:1), their adsorption behaviors for two typical dissolved gases, CO and C2H2, were studied. The CO and C2H2 molecules were placed at an initial atomic distance of about The geometry of the nanosurface was optimized to determine the optimal configuration (MPC) for gas adsorption and further analysis was performed. The MPC was determined to be the nanosurface with the most negative adsorption energy (E ad ) configuration, according to this definition E ad The calculation formula is:
[0096] E ad =E surface / gas -E surface -E gas .
[0097] In the formula, E surface / gas is the total energy of gas adsorption of MoS2, WS2 or MoS2-WS2, E surface is the total energy of the nanosurface, i.e., MoS2, WS2, or MoS2-WS2, E gas is the total energy of the separated gas molecules.
[0098] By E ad The MPC of CO and C2H2 molecules adsorbed on the three nanosurfaces can be determined by using the equation, and the charge density difference (CDD) of the MPC can be plotted to better understand the charge transfer behavior and binding force between the nanosurface and the gas. Fig. 9 The MPC and CDD of CO and C2H2 adsorption on MoS2 and WS2 surfaces are plotted.
[0099] Fig. 9 The adsorption of CO and C2H2 on the MoS2 monolayer shows that the CO molecule is basically parallel to the MoS2 surface with a small slope, while the C2H2 molecule is completely parallel to the MoS2 surface. The molecule-surface distances of the two systems are 3.20 and Such a long distance means that the interaction between MoS2 and the two gases is weak, so no new bonds are formed between them. According to the definition of adsorption energy, the adsorption of CO and C2H2 to lead in MoS2 systems is calculated to be -0.08 and -0.17 eV, respectively. In these two systems, E adsThe absolute value of is so small, indicating the presence of physical adsorption, in which van der Waals forces play a dominant role in gas-surface interactions. From the CDD of the two systems, it can be seen that there is a certain amount of electron accumulation on the CO and C2H2 molecules, which indicates that they have electron-accepting properties when interacting with the MoS2 surface. In addition, in the C2H2 system, in addition to the MoS2 surface, there is also a certain degree of electron loss, which indicates that the C2H2 system has the electron loss characteristics of the nanosurface and has a stronger charge transfer behavior than the CO system. The charges of CO and C2H2 molecules are -0.016 and -0.020e, respectively, which reveals from a quantitative perspective the charge transfer path from MoS2 to the two gas molecules and the stronger electron acceptance of C2H2 molecules than CO molecules.
[0100] For the adsorption of CO and C2H2 on WS2 monolayer, the adsorption configurations of both systems, including adsorption position and molecular orientation, are similar to those on MoS2 monolayer. However, the molecular surface distance of WS2 / gas system is slightly longer than that of MoS2 / gas system, and that of CO system is The C2H2 system is This indicates that WS2 has weaker adsorption performance than MoS2 for the two gas molecules. This assumption can be confirmed by calculating E ad To verify, the results obtained are -0.01eV and -0.09eV respectively. From this point of view, the adsorption of CO and C2H2 on the WS2 monolayer can also be determined. At the same time, the CDD distribution of the WS2 / gas system is similar to that of the MoS2 / gas system. In addition, the charge transfer behavior in the WS2 / gas system is also the same as that in the MoS2 / gas system, where both CO and C2H2 exhibit electron-accepting properties, obtaining 0.016 and 0.021e of electrons from the WS2 surface.
[0101] With the adsorption of CO and C2H2 on the MoS2-WS2 heterostructure, there are three adsorption sites, namely on the MoS2 side, the MoS2-WS2 junction and the WS2 side. The optimized adsorption models of the three adsorption sites are as follows: Fig.10 As shown in the figure, whether on the MoS2 side, the WS2 side, or above the MoS2-WS2 interface, the adsorption configurations of CO and C2H2 on the MoS2-WS2 surface are very similar to those on the MoS2 or WS2 surface. The difference is that the molecular surface distance on the MoS2-WS2 surface is slightly shorter than that on the MoS2 or WS2 surface. Specifically, in the CO adsorption system, the shortest molecular surface distance is at the MoS2-WS2 interface. Next is the MoS2 side The longest side is WS2 In the C2H2 adsorption system, they are: MoS2-WS2 junction side side According to E ad The calculation results show that the adsorption of CO and C2H2 on the MoS2-WS2 structure is more inclined to the heterojunction position of MoS2-WS2, and its E ad At the same time, it should be noted that the adsorption energies of CO and C2H2 through the MoS2 side (-0.14 eV and -0.23 eV) and WS2 side (-0.10 eV and -0.21 eV) are very different from those on the MoS2-WS2 heterojunction; these E ads It shows that the adsorption performance of MoS2-WS2 heterostructure for CO and C2H2 molecules at each site is stronger than that of MoS2 and WS2. That is, the heterostructure between MoS2 and WS2 can enhance their gas adsorption performance, especially for gas adsorption at the heterojunction.
[0102] Fig.11 The differential charge density (CDD) of CO and C2H2 adsorbed at the junction of the MoS2-WS2 heterostructure, that is, at the optimized adsorption site, is shown. As can be seen from the figure, the electron aggregation is mainly located on the CO and C2H2 molecules, indicating that their electron-withdrawing properties interact with the MoS2-WS2 heterojunction; the electron density between the gas and the nanosurface is much higher than that of the MoS2 or WS2 system, indicating that the electron-donating performance of the MoS2-WS2 heterojunction to transfer electrons to the gas is stronger. According to the Hirshfeld population analysis, it can be found that the CO and C2H2 molecules on the MoS2-WS2 surface carry negative charges of 0.025 and 0.034e, respectively. This confirms that the amount of charge transferred from the MoS2-WS2 surface to the gas is larger than the amount of charge transferred from the MoS2 or WS2 surface to the gas. That is, the MoS2-WS2 surface exhibits stronger chemical reactivity and electron mobility than the isolated MoS2 or WS2 surface, and the CO and C2H2 molecules still act as electron acceptors.
[0103] Compared with isolated MoS2 or WS2 surfaces, the MoS2-WS2 heterostructure has stronger adsorption performance for CO and C2H2, larger absolute value of adsorption energy, and larger amount of charge transferred from the nanosurface to the gas molecules. It can be concluded that the heterojunction is a feasible nanomaterial structure to promote the adsorption behavior of gases on the surface of gas-sensitive materials.
[0104] like Fig.12As shown in the figure, from the BS distribution of gas adsorption MoS2 and WS2 systems, it can be seen that after adsorption of CO and C2H2, the band gap of MoS2 decreases to 1.651eV; after adsorption of C2H2, the band gap decreases to 1.645eV; and after adsorption of CO and C2H2, the band gap of WS2 increases to 1.864eV. In other words, the band gap of MoS2 decreases by 0.18% in the CO system, the band gap of MoS2 decreases by 0.54% in the C2H2 system, and the band gap of WS2 increases by 0.87% in both CO and C2H2 systems. Although the change in the band gap after gas adsorption can adjust the conductivity of MoS2 or WS2, these small changes will not produce significant or obvious electrical responses for sensitive detection. On the other hand, after the adsorption of CO molecules, the band gap of the MoS2-WS2 heterostructure decreases to 1.486 eV (a decrease of 14.94%), and after the adsorption of C2H2 molecules, the band gap decreases to 1.352 eV (a decrease of 22.71%). It can be calculated that the band gap change rate of the gas adsorbed MoS2-WS2 system is several times that of the gas adsorbed MoS2 or WS2 system (CO is 82.4 times that of MoS2 and 17.2 times that of WS2; C2H2 is 42.1 times that of MoS2 and 26.1 times that of WS2). Therefore, the conductivity change of the MoS2-WS2 heterostructure after gas adsorption will be much larger and is feasible for sensitive CO and C2H2 detection, resulting in higher sensing response. In all gas adsorption systems, the top valence band and the bottom conduction band are located at the same point, which indicates that gas adsorption has no effect on the direct semiconductor properties of isolated MoS2 and WS2 and the heterostructure of MoS2-WS2. The band gap of the gas adsorption system and the rate of change from the isolated nanosurface to the gas adsorption system are shown in Table 1.
[0105] Table 1 Band gap and change rate of gas adsorption on MoS2, WS2 and MoS2-WS2 system
[0106]
[0107] The change in the conductivity (resistance) of nanomaterials provides the basic sensing mechanism for resistive gas sensors because the conductivity (σ) of the nanosurface is proportional to its band gap (B g ) is related as shown below:
[0108]
[0109] Where λ is a constant, T is the temperature, and k is the Boltzmann constant (1.38×10 -23J / k). It can be seen from the formula that after the adsorption of CO and C2H2, the resistance of MoS2 and MoS2-WS2 decreases, while after the adsorption of CO and C2H2, the resistance of WS2 increases. In addition, based on the change of nanosurface conductivity, the sensing response (S) of the nanomaterial gas sensor can be calculated by the following formula:
[0110] S=(σ gas -1 -σ pure -1 )σ pure -1 .
[0111] Among them, σ gas and σ pure are the conductivity of the gas adsorbed nanosurface and the isolated nanomaterial (i.e., MoS2, WS2, and MoS2-WS2 isolated in this work), respectively. According to the above formula, at room temperature (298K), the sensing responses of MoS2, WS2, and MoS2-WS2 for CO and C2H2 detection are as follows: Fig.13 shown.
[0112] from Fig.13 It can be seen that MoS2 and MoS2-WS2 show negative sensing responses to CO and C2H2, while WS2 shows positive sensing responses to the two gas molecules. Among them, the sensing responses of the MoS2-based gas sensor for detecting CO and C2H2 are -5.67% and -16.07%, respectively. However, this sensing response is somewhat small, and the changes cannot be detected and checked by the host computer. The sensing response of the WS2-based gas sensor for both CO and C2H2 is 36.55%. These values are moderate for gas detection, so it can be assumed that WS2 has a certain potential and can be used as a resistive gas sensor to detect typical dissolved gases. In addition, the sensing responses of the MoS2-WS2 system adsorbed with CO and C2H2 are -99.56% and -99.95%, respectively, indicating that after adsorbing CO or C2H2 molecules, the resistance of MoS2-WS2 will be greatly reduced by nearly 1 times. This reveals the strong potential of MoS2-WS2 to explore resistive gas sensors on these two materials, with greatly enhanced sensing responses compared to MoS2 or WS2.
[0113] In addition, in order to study the reusability of MoS2-WS2 for sensing CO and C2H2 gases, the recovery time (τ) required for their desorption from the MoS2-WS2 surface was calculated based on the van,t-Hoff-Arrhenius theory, and the calculation formula is:
[0114]
[0115] Where A is the trial frequency (1012 s -1 ), k is the Boltzmann constant, and T is the temperature. From the above equation, it can be seen that the time required for the desorption of CO and C2H2 in the MoS2-WS2 heterostructure at room temperature (298K) is 0.34 and 16.84ns, respectively. These findings indicate that the MoS2-WS2 supercell has good recycling properties and can desorb one gas molecule from its surface, so it can be assumed that MoS2-WS2 is a reusable gas detection sensing material. Based on the current analysis, it can be concluded that the MoS2-WS2 heterostructure is an excellent resistive gas sensor with good reliability at room temperature.
[0116] It was finally found that compared with the separated MoS2 and WS2, the MoS2-WS2 heterostructure (W ion: Mo ion = 1.4:1) has stronger adsorption and charge transfer properties. ad -0.15 and -0.25 eV respectively, Q T are -0.025 and -0.034e, respectively. Compared with the gas-adsorbed MoS2 or WS2 systems, the electronic properties of the MoS2-WS2 heterostructure are significantly deformed, resulting in a more obvious change in the band gap. At room temperature, the detection responses of MoS2-WS2 for CO and C2H2 are -99.56% and -99.95%, respectively, and the desorption recovery times of CO and C2H2 are 0.34 and 16.84ns, respectively. These findings show the strong potential of the MoS2-WS2 heterostructure as a good reusable CO and C2H2 gas sensor, paving the way for further exploration of the application of TMDs-based heterostructures in gas-sensing applications, especially in dissolved gas analysis in oil-immersed transformer power equipment.
[0117] The gas-sensing characteristics of the gas sensor according to the embodiment of the present invention are studied below.
[0118] like Figure 5As shown in the figure, a gas-sensing performance test experimental platform is constructed to conduct gas-sensing tests on the prepared gas sensors. It consists of the gas to be tested, a program-controlled dynamic gas distribution system (Mass Flow Control, MFC), a gas-sensing test analysis system and an exhaust gas treatment system. The specific test process is as follows: First, with dry air as the background, the response values of each sensor unit to three gases dissolved in oil, H2, C2H2 and C2H4, at different working temperatures at a concentration of 50ppm are tested respectively, where the working temperature is at intervals of 30℃, from room temperature (about 25℃) to 300℃. According to the different temperature response values, the optimal working temperature of the sensor unit for each component is determined, and at this temperature, the response values at different concentrations (0-100ppm, 10ppm intervals, and the test interval at low concentrations is further adjusted with the sensor performance), response / recovery characteristics, and repeatability are measured. By testing the response values of different concentrations of each component, the sensitivity of each sensor unit to different components is calculated, and the detection limit of each component is calculated in combination with the background noise, and the gas-sensing performance of different sensor units is compared.
[0119] The dissolved gases in transformer oil are mainly H2, C2H2 and C2H2. The molecular structure of the dissolved gases in oil is as follows: Figure 6 As shown in the figure, a represents H2; b represents C2H2; c represents C2H4.
[0120] Since a single sensor unit has cross-interference with different components, it is impossible to perform more accurate concentration detection on multiple components. Therefore, it is necessary to construct a sensor array composed of multiple sensor units, conduct a large number of gas-sensitive tests, and achieve high-precision quantitative detection of mixed gas components and concentrations by finding the correlation between the sensor array and the gas to be tested. Figure 8 As shown, on the one hand, this process requires obtaining a large number of reliable training samples, and on the other hand, it is necessary to select and optimize a reliable mixed gas pattern recognition method.
[0121] First, a multi-element sensor array based on different modified TMDCs was built, and mixed gas test samples were obtained. The array assembly method is: for the three components, four gas-sensitive materials with high sensitivity and good recovery were selected, and fixed at the working temperature with the highest sensitivity for the component. Considering the consistency of the sensor unit preparation method, three sensor units were prepared for each gas-sensitive material. Therefore, the sensor array contains a total of 36 sensor units of 12 gas-sensitive materials, which can be automatically tested in parallel with unattended high throughput. The concentrations of the three characteristic components are set as follows: 0ppm, 0.2ppm, 0.5ppm, 1ppm, 2ppm, 5ppm, 10ppm, 20ppm, and 50ppm. Because the combination method reaches 9×9×9=729, in order to improve the test efficiency, a three-factor nine-level high-intensity orthogonal test table is used to obtain 81 groups of test concentrations, as shown in Table 2. The entire test process can be automated by program to perform gas distribution and sensor data sampling.
[0122] Table 2 Concentration levels of each gas sample (ppm)
[0123]
[0124] To facilitate the analysis and comparison of the characteristic values of each sensing unit and reduce the neuron saturation, it is necessary to normalize the characteristic values of each sensing data sample to the same order of magnitude. The specific method is as follows:
[0125]
[0126] In the formula, N and n are the normalized value and the value before normalization respectively, and min[n i and max[n i are the minimum and maximum values of the array before normalization.
[0127] The CNN adopts the Adam optimizer, and the ReLU activation function is used in the convolutional layer. The CNN flattens and extracts features from the dynamic response curve, and adds environmental condition variables such as humidity, air pressure, and long-term usage time to correct the drift features, which are used as the input layer of the DBN (Deep Belief Network) to further suppress the drift. Then it enters the DBN stacked by three RBMs (Restricted Boltzmann Machines). The DBN is trained through unsupervised learning, and then the structure in the DBN is fine-tuned using supervised learning. Specifically, it is divided into two stages. One is to train the intermediate hidden parameters using the Contrastive Divergence method, and the other is to fine-tune the network weights and biases using stochastic gradient descent. Finally, the DBN is connected to the fully connected layer to achieve the qualitative analysis of gas mixture classification through the softmax function. The classification model classifies each component into three categories, namely none (0 ppm), low concentration (0 ppm < C < 10 ppm), and high concentration (C ≥ 10 ppm), a total of 27 categories, and marks the input samples. The loss function of classification prediction uses the Cross Entropy loss. The working principle of the DBN algorithm model is as Figure 7 shown.
[0128] For regression prediction, samples were labeled with linear normalized concentrations of 0 to 50 ppm. CNN was trained as a regression network, and the structure and parameter settings were the same as the classification algorithm. The number of RBM stacks in DBN remained unchanged, and only the last layer output was a regression output with three neurons, which provided normalized concentration values of three components H2, C2H2 and C2H4 respectively. For each component, the loss function for concentration prediction was the root mean square error (RMSE). All training sets and test sets in classification and regression were divided into 80% and 20% and a 5-fold cross validation was performed to prevent overfitting. Finally, the classification accuracy based on CNN-DBN was compared with the RMSE parameters of the regression algorithm and a variety of scikit-learn machine learning methods and BPNN to verify the accuracy of the model.
[0129] The technical solution of the present invention is further described below with reference to specific embodiments.
[0130] Example 1
[0131] The gas sensor prepared in Example 1 has an aluminum oxide substrate with a size of 4×6×0.5 mm. 3 The substrate has stable chemical properties and can be reused for a long time. The spacing between the platinum interdigitated electrodes is 0.15 mm. The pn junction modified TMDCs gas-sensitive material is a MoS2-WS2 heterostructure. The molar ratio of W ions to Mo ions in the pn junction modified TMDCs gas-sensitive material of this embodiment is 1.3:1.
[0132] Example 2
[0133] The gas sensor prepared in Example 2 has an aluminum oxide substrate with a size of 4×6×0.5 mm. 3 The substrate has stable chemical properties and can be reused for a long time. The spacing between the platinum interdigitated electrodes is 0.15 mm. The pn junction modified TMDCs gas-sensitive material is a MoS2-WS2 heterostructure. The molar ratio of W ions to Mo ions in the pn junction modified TMDCs gas-sensitive material of this embodiment is 1.4:1.
[0134] Example 3
[0135] The gas sensor prepared in Example 3 has an aluminum oxide substrate with a size of 4×6×0.5 mm. 3 The substrate has stable chemical properties and can be reused for a long time. The spacing between the platinum interdigitated electrodes is 0.15 mm. The pn junction modified TMDCs gas-sensitive material is a MoS2-WS2 heterostructure. The molar ratio of W ions to Mo ions in the pn junction modified TMDCs gas-sensitive material of this embodiment is 1.5:1.
[0136] Example 4
[0137] The gas sensor prepared in Example 4 has an aluminum oxide substrate with a size of 4×6×0.5 mm. 3 The substrate has stable chemical properties and can be reused for a long time. The spacing between the platinum interdigitated electrodes is 0.15 mm. The pn junction modified TMDCs gas-sensitive material is a MoS2-WS2 heterostructure. The molar ratio of W ions to Mo ions in the pn junction modified TMDCs gas-sensitive material of this embodiment is 1.6:1.
[0138] Example 5
[0139] The gas sensor prepared in Example 5 has an aluminum oxide substrate with a size of 4×6×0.5 mm. 3 The substrate has stable chemical properties and can be reused for a long time. The spacing between the platinum interdigitated electrodes is 0.15 mm. The pn junction modified TMDCs gas-sensitive material is a MoS2-WS2 heterostructure. The molar ratio of W ions to Mo ions in the pn junction modified TMDCs gas-sensitive material of this embodiment is 1.7:1.
[0140] The performance tests of the gas sensors prepared in Examples 1 to 5 include indicators such as sensitivity, response time and recovery time. Specifically, the prepared sensors are applied in actual detection of dissolved gas in oil, and their response time, recovery time and sensitivity to gases of different concentrations are recorded. The test environment should simulate actual application conditions to ensure the reliability of the data. MoS2-WS2 heterostructures with different doping ratios are prepared by adjusting the molar ratio of W ions to Mo ions, and applied to gas sensors for detecting dissolved gas in oil. By precisely controlling the raw material ratio and preparation conditions, a stable and reliable gas sensor can be obtained.
[0141] In summary, the embodiments of the present invention utilize transition metal disulfides as core sensing materials, and successfully synthesize intrinsic and pn junction modified TMDCs with optimized performance by adopting staged hydrothermal and high-temperature sulfurization methods; by finely controlling key parameters in the synthesis process such as temperature, time and raw material ratio, high-quality preparation of WS2 and MoS2 is achieved; by adjusting the ion ratio of W and Mo, a MoS2-WS2 heterostructure is formed, which significantly improves the sensitivity and selectivity of the sensor to dissolved gases in oil; compared with the prior art, the gas sensor of the embodiment of the present invention shows obvious performance advantages in detection lower limit, response speed and stability, demonstrating its broad potential in practical applications, and has important practical value in the fields of oil monitoring and environmental protection.
[0142] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A gas sensor for detecting dissolved gas in oil, characterized in that: include: A substrate, interdigital electrodes deposited on a surface of the substrate, and a pn junction modified TMDCs gas-sensitive material attached to a surface of the interdigital electrodes; The pn junction modified TMDCs gas-sensitive material is a MoS2-WS2 heterostructure material, and the molar ratio of W to Mo in the MoS2-WS2 heterostructure material is 1.3:1 to 1.7:
1.
2. The gas sensor for detecting dissolved gas in oil according to claim 1, characterized in that: The molar ratio of W to Mo in the MoS2-WS2 heterostructure material is 1.4:
1.
3. A method for preparing a gas sensor for detecting dissolved gas in oil, characterized in that: include: Preparing a pn junction modified TMDCs gas-sensitive material, wherein the pn junction modified TMDCs gas-sensitive material is a MoS2-WS2 heterostructure material, and the molar ratio of W to Mo in the MoS2-WS2 heterostructure material is 1.3:1 to 1.7:1; Mixing and grinding the pn junction modified TMDCs gas-sensitive material and ethylene glycol to obtain a mixed solution; depositing interdigitated electrodes on the surface of the substrate; The mixed solution was uniformly coated on the surface of the interdigital electrode and then dried at 150° C. for 12 h to obtain a gas sensor.
4. The method for preparing a gas sensor for detecting dissolved gas in oil according to claim 3, characterized in that: The step of preparing the pn junction modified TMDCs gas-sensitive material comprises: Prepare WO3·H2O and MoO3 respectively; Weigh the prepared WO3·H2O and MoO3 according to the molar ratio of W to Mo; The weighed WO3·H2O and MoO3 are respectively sulfurized with S powder at 800° C. for 2 h in an inert gas atmosphere, and then the sulfurized products are contacted or stacked to obtain the pn junction modified TMDCs gas-sensitive material.
5. The method for preparing a gas sensor for detecting dissolved gas in oil according to claim 4, characterized in that: The preparation process of WO3·H2O comprises: Na2WO4·2H2O, H2C2O4·2H2O and HCl were heated at 92°C for 6 h, and then WO3·H2O was obtained by filtering, washing and drying.
6. The method for preparing a gas sensor for detecting dissolved gas in oil according to claim 4, characterized in that: The preparation process of MoO3 comprises: Heating (NH4)2M2O7·2H2O at 500℃ for 2h in air atmosphere gave a solid product; The solid product, H2O2 and CTAB were heated at 50°C for 2 h, and then MoO3 was obtained by filtration, washing and drying.
7. The method for preparing a gas sensor for detecting dissolved gas in oil according to claim 3, characterized in that: The step of preparing the pn junction modified TMDCs gas-sensitive material comprises: Na2WO4·2H2O, H2C2O4·2H2O and HCl were mixed and heated at 92°C for 6 h, and then WO3·H2O was obtained by filtering, washing and drying; WO3·H2O and (NH4)2M2O7·2H2O were weighed according to the molar ratio of W to Mo; The weighed WO3·H2O and (NH4)2M2O7·2H2O are sulfurized with S powder at 800° C. for 2 h under an inert gas atmosphere to obtain the pn junction modified TMDCs gas-sensitive material.
8. The method for preparing a gas sensor for detecting dissolved gas in oil according to claim 3, characterized in that: The step of preparing the pn junction modified TMDCs gas-sensitive material comprises: Using carbon sphere template, Na2WO4·2H2O and (NH4)2M2O7·2H2O were reacted at 180℃ for 12h to synthesize carbon sphere composite of WO3 and MoO3 through hydrothermal-template method. The carbon sphere composite of WO3 and MoO3 was calcined at 600℃ for 4h to remove the carbon sphere template and obtain a hollow solid. The pn junction modified TMDCs gas-sensitive material is obtained by sulfurizing the hollow solid with S powder at 500° C. for 12 hours under an inert gas atmosphere.
9. A microsensor array, characterized in that: include: A plurality of gas sensors according to any one of claims 1 to 2.
Citation Information
Cited By
Ternary heterogeneous composite gas-sensitive material, preparation method thereof and application of ternary heterogeneous composite gas-sensitive material in detection of SF6 decomposition product H2S
CN122562053A
A ternary heterojunction composite gas sensitive material, a preparation method thereof and application thereof in detecting SF6 decomposition product H2S
CN122562053B